Michael Chu with Simona Paiva a client of Emprender, ACCIONs' affiliate in Argentina, 1997 - West, Don (Tufts Archival Research Center, 2016)
This date is approximate. Images should be used only in an Editorial (non-commercial) context with photo credit (© DON WEST).